Islam Nusantara as Moderatand Tolerant Islam: a Literature Research - Qodir, Zuly (Faculty of Tarbiyah and Education, Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2016)
Some questions are raised by foreign researchers and observers about Islam of Indonesia. After literature survey was done, it’s concluded that format of the Indonesian Islam is moderate and tolerate one. This is viewed in its characteristic doesn’t support the method of coercion, eviction, and destruction of the religious tradition existing before Islam came to Indonesia in developing it in archipelago, before it changes to Indonesia. The accommodative characteristic of the Islam developed by the clergy (religious figure) such as walisongo in Java Island, the religious figure (muballigh) from the Middle East in Indonesia and also the muballigh after walisongo coming from Muhammadiyah and NU. Islam never discredited another religion even though it’s different. So, the culture developed is the moderate and tolerate culture even though it aims to do renewal about which one is not suitable with Islam. The literature done in this writing has shown the characteristic of the Indonesian Islam which is known also with the term Islam of archipelago (Islam Nusantara).